Effect of Preanesthetic Assessment Timing on Preoperative Anxiety in Ambulatory Surgery Patients - Bülent Serhan Yurtlu; Şule Özbilgin; Volkan Hancı; Nazire Ateş Ayhan (Hitit Medical Journal)
Objective: Preoperative anxiety is a prevalent concern among ambulatory surgery patients. Besides controversialfindings between preoperative anesthesia evaluation and anxiety in ambulatory surgical patients, its optimaltiming on anxiety levels remains unclear. This study aimed to explore the impact of preoperative anesthesiaevaluation timing on anxiety levels in patients undergoing ambulatory surgery.Material and Method: A prospective, non-randomized, observational study was conducted between May 2016 andAugust 2016. Adult patients scheduled for elective surgery under local anesthesia with sedation were included.Participants were divided based on the timing of anesthesia evaluation: Group OP (evaluated before surgery) andGroup AS (assessed on the day of surgery). Preoperative anxiety was measured using the Spielberger State-TraitAnxiety Inventory (STAI) and Visual Analog Scale (VAS) at two time points: just before preoperative anesthesiaevaluation (Score 1) and immediately before surgery (Score 2).Results: The study comprised 144 patients, with 72 in each group. No significant differences between groupswere observed in baseline sociodemographic characteristics (p>0.05), except for significantly older patientsin Group OP than those in Group AS (p=0.030). Median STAI-S, STAI-T, and VAS scores (Score 1) showed nosignificant differences between groups (p>0.05). Both groups significantly increased STAI-S scores betweenScore 1 and Score 2 measurements (p=0.015 for Group OP and p